Fluorescent spongy carbon nanoglobules derived from pineapple juice: A potential sensing probe for specific and selective detection of chromium (VI) ions. Issue 9 (15th June 2017) - Sharma, Shelja; Umar, Ahmad; Mehta, Surinder Kumar; Kansal, Sushil Kumar
Abstract: Herein, we report, for the first time, the facile, green and one step hydrothermal synthesis of fluorescent spongy carbon nanoglobules (CNG) derived from pineapple juice as a sole carbon source without involving any strong acid treatment. The synthesized CNG not only exhibits hydrophilicity and can remain stable for several weeks but also demonstrates prominent blue color fluorescence under UV light (λ=365 nm). These CNG showed wide range of emission spectra in the visible region depending upon the different excitation wavelengths. The synthesized CNG were characterized in detail in terms of their morphological, structural, optical, compositional and thermal properties using numerous analytical and spectroscopic techniques. For application point of view, the perspective to utilize CNG as fluorescent sensing probe has also been explored with the introduction of various highly toxic metal ions and interestingly, it was observed that the fluorescence intensity of CNG was drastically quenched by chromium (VI) ions with high selectivity over the linear range of concentrations 0–18 µM with stern volmer constant 2.29×10 4  M −1 . Such encouraging results revealed that simply prepared CNG are potential scaffold to fabricate highly sensitive and selective fluorescent sensors for the detection of highly hazardous and life threatening metal ions.